Approaches to Measuring the Efficiency of the Bulgarian Libraries - Rusinova, Evgeniya (Qualitative and Quantitative Methods in Libraries, 2017)
The challenge of evaluating library activities is crucial when introducing new technologies in the library field. Long underestimated in terms of intensive adaptation of the Bulgarian libraries to the challenges of new technologies and the need to respond to the needs of the patrons, this process is becoming crucial to their survival. Its importance is growing in the process of intensive digitization of library stock. The need to construct relevant to consumer demand libraries, as well as the introduction of the system of quality management of library work (TQM) highlights in the library practice the issues of library efficiency. The text presents the specifics of the application of qualitative and quantitative methods to study the efficiency of the Bulgarian libraries, and in particular, the relation of the success of the library PR and the marketing activities to such studies. The emphasis is on the process of linking the introduction of innovative approaches with the impact of current trends of global library practices. Highlighted is the role of measurement of library efficiency in terms of library management and strategic planning in libraries. The challenges that arise throughout the study of the efficiency of different types of libraries are also brought to the fore, as well as the pitfalls in adapting the foreign experience that has been borrowed. Some of the difficulties associated with measuring library efficiency have been pointed out.  The presented findings and conclusions are based on research of the practices in various types of libraries – public, university and specialized research ones.